The ratio between the screw distance and femoral neck width on lateral radiography is a reliable predictor of femoral head necrosis: a clinical review and corresponding numerical simulations - Hong Li; Shengyu Wan; Jian Zhang; Fan Wu; Xiaozhong Luo; Chao Wu; Xu Lin; Jingchi Li (Journal of Orthopaedic Surgery and Research)
Abstract Background Fixation instability serves as an initial trigger for femoral head necrosis in patients with femoral neck fractures undergoing internal fixation. The configuration of screw trajectories is critical in determining the stability of the fixation. Our previously published study indicates that abduction of screw trajectories may enhance postoperative angular stability. However, the effectiveness of a wider screw distribution on the sagittal plane in optimizing fixation stability and reducing the risk of femoral head necrosis remains uncertain. Methods This retrospective study reviewed imaging data from patients with femoral neck fractures who were treated with inverse triangle cannulated screw fixation. Postoperative lateral radiographs were used to evaluate the screw configuration strategy. The distance between the two cranial screws and the femoral neck width at its narrowest point were measured. The ratio of these two measurements was calculated to represent the screw spread grade. Demographic and imaging parameters were compared between patients who developed femoral head necrosis and those who did not. Regression analysis was conducted to identify potential risk factors associated with femoral head necrosis. Additionally, numerical models were employed to simulate the biomechanical impact of variations in screw spread grade. Results The clinical analysis revealed that a lower screw distance-to-femoral width ratio was associated with a higher incidence of femoral head necrosis. This ratio was also identified as an independent risk factor for femoral head necrosis. Biomechanical simulations corroborated these findings, demonstrating that models with a lower screw-to-femoral width ratio exhibited reduced fixation stability and increased stress distribution. Conclusions Wider distribution of screws along the sagittal plane may significantly mitigate the risk of femoral head necrosis by enhancing fixation stability. The optimization of screw trajectories, particularly through broader screw spacing facilitated by a navigation system, emerges as a promising strategy for improving the local biomechanical environment and reducing the likelihood of femoral head necrosis.